Social Networks Among the Urban Poor: Inequality and Integration in a Latin American City - Espinoza-Espinoza, V (Taylor and Francis, 2018)
A persistent social crisis has characterized many Latin American countries since the eighties, from Argentina and Chile in the south to Mexico before and after its free-trade agreement with North America. Most of the crisis has coincided with the implementation of deep economic changes, known as structural adjustment, aimed at stabilizing national economies (Morales and McMahon 1993). The market allocation of resources has been the ubiquitous response of economists and conservative policymakers to overcome inefficient public spending, debt crises, hyperinflation, recession, unemployment, and other economic disequilibria affecting the population’s well-being. Promoted by such institutions as the International Monetary Fund (IMF), the American government and Thatcherism, these economic policies have attempted “to subordinate the substance of society itself to the laws of the market” (Polanyi 1957a, p. 72). © 1999 Taylor & Francis. All rights reserved.